The Role of Human Resources Competence in Improving Quality of The Financial Reports of The Indonesian State-Owned Enterprises - Nasution, Yan Noviar; Supriadi, Yoyon (Institut Bisnis dan Informatika Kesatuan, 2024)
This study investigates the influence of human resource competence on the quality of accounting information systems and its subsequent impact on the quality of financial reports in Indonesian State-Owned Enterprises (SOEs). Using the Structural Equation Modeling (SEM) approach with LISREL software, the findings reveal that human resource competence significantly enhances the quality of accounting information systems. In turn, the improved quality of accounting information systems contributes positively to the quality of financial reporting. Moreover, the study demonstrates that human resource competence also has a direct and indirect effect—mediated by the accounting information system—on the quality of financial reports. These results highlight the critical role of competent human capital in ensuring transparent, accurate, and timely financial reporting within SOEs. Keywords: human resource competence; accounting information systems; financial reporting quality; transparency; State-Owned Enterprises.